Lay off employees or terminate consultant contracts? Responses to an external shock in three firms in the Norwegian petroleum industry. Issue 7 (6th November 2017) - Fijalkowska, Anna Paula; Hjartåker, Karina Sofie; Nesheim, Torstein
Abstract : Purpose: Previous studies on non-standard employment relations have analyzed how firms' use of non-standard work arrangements are explained by variables related to numerical flexibility. Here, the purpose of this paper is to explore how firms respond to changes in the external environment through reduction in staffing. Since the firms combine employees and external consultants, they are confronted with a dilemma between laying off employees or terminating consultant contracts. Design/methodology/approach: The empirical context is the petroleum sector in Norway. The data consists of 11 interviews with managers at different levels in three firms. Findings: The authors found that firms terminated over 80 percent of the consultant contracts, while around a forth of employees were downsized. A core-periphery strategy and union power are vital drivers of the prioritization of employees. However, some consultants were retained due to their knowledge of unique aspects of the firm and their role in development and innovation. The authors also found that the firms differed in their emphasis on seniority vs competencies criteria in deciding "survival" among employees. Research limitations/implications: A main contribution of the study is thus the identification of variables and mechanisms that influence the two interrelated choices of downsizing in such multi-employment contexts. The main limitation is the number of firms analyzed (three), which restricts statistical generalization. Practical implications: Better understanding of circumstances and criteria of downsizing choices in employees/external consultants' constellations. Originality/value: This study is one of the first to analyze two interrelated issues of downsizing in such constellations lying off employees vs terminating consulting contracts, and whether seniority or competence criteria were prioritized when laying off employees. A main contribution of the study is the identification of variables and mechanisms that influence the two interrelated choices of downsizing in such multi-employment contexts.